Cytokine, physiological, technical–tactical and time structure responses in simulated judo competition - Franchini, Emerson; Lira, Fabio Santos [UNESP]; Julio, Ursula Ferreira; Antunes, Barbara Moura [UNESP]; Agostinho, Marcus Fabio; Shiroma, Seihati Ari; Gonçalves Panissa, Valéria Leme (Taylor & Francis, 2018)
This study investigated physiological modulation on metabolic and inflammatory parameters, the technical–tactical and time structure variables, across a simulated judo competition. Ten judokas were submitted to a simulated competition (four matches), with blood collection in time zero, after each match, and 30 and 60 min post the fourth match. Before each match the rating of perceived recovery (RPR) and after each match the rating of perceived exertion (RPE) and heart rate (HR) were collected; lactate concentration before and after each match was collected. There was no difference across matches for RPR, RPE, HR, technical–tactical, time structure, interleukin (IL)-10, MCP-1, TNF-α, cortisol, testosterone and testosterone–cortisol ratio. Higher lactate was found post-match compared to prematch. Moreover, lactate was higher pre-third than the pre-first match, and post-second than post-third and fourth matches. Glucose was higher post-second match compared to prematches and 30-min post-fourth match; IL-6 was higher post-third, post-fourth and post-30 and 60-min fourth match than prematches and also higher post-first match compared to post-third and 60-min post-fourth match. Thus, alterations observed in glucose, lactate and IL-6 judo competition seem to be related to metabolism regulation to maintain the technical–tactical actions across the matches.
Keywords: glucose; hormones; IL-6; technical–tactical action; time structure variables